KEPUASAN KERJA TERGANTUNG DARI KINERJA MANAJERIAL DAN PARTISIPASI PENGANGGARAN (Studi Pada Koran Harian Pagi Radar Kediri) - Anita Sumelvia Dewi (Politeknik Negeri Batam, 2018)
ABSTRACT This study aims to analyze how the influence of budget participation variables on managerial performance and job satisfaction. This research development from research of Wasisto and Sholihin (2004), In this research, Data used is primary data with spread questioner to respondent. From the questionnaires collected respondents obtained from employee perceptions and newspaper journalists Radar Kediri including middle managers and managers on it. During the study, of the 70 questionnaires distributed, the 58 questionnaires (78.6%) returned, but only 44 questionnaires answered completely so that the sample of this study was 44 people. Analysis of this research with Moderating Regression Analysis (MRA). The results in this study indicate that budgetary participation reinforces managerial performance and job satisfaction when budgetary participation interacts with procedural justice as a moderating variable, therefore the influence will be stronger and more significant. So the researcher concludes that there is influence between budget participation on managerial performance. Managerial performance also has a significant effect on job satisfaction.